Self-Regulated Learning in Mathematics Education: A Systematic Review of Its Contribution to Mathematical Competencies and Learning Outcomes - Atilla Divani Davel; Adi Ihsan Imami; Alpha Galih Adirakasiwi (Jurnal Didactical Mathematics, 2026)
Self-regulated learning (SRL) is widely recognized as an essential factor in mathematics learning; however, empirical evidence remains fragmented across mathematical competencies, educational contexts, and dimensions of self-regulation, limiting a comprehensive understanding of its role in mathematics education. This systematic literature review synthesizes empirical evidence to examine the contribution of SRL to mathematics learning, identify the mathematical competencies most consistently associated with SRL, and characterize the dominant dimensions of students’ self-regulation. Following the PRISMA guidelines, 20 empirical studies published between 2021 and 2025 were systematically selected and synthesized using narrative thematic analysis. The findings consistently demonstrate positive associations between SRL and mathematics achievement, reasoning, creative thinking, conceptual understanding, and problem-solving performance. Planning, goal setting, self-monitoring, and self-evaluation emerged as the most prominent dimensions of SRL, whereas learning initiative was identified as the least developed aspect across the reviewed studies. Beyond supporting academic performance, the synthesis indicates that SRL functions as an integrated regulatory mechanism through which cognitive, metacognitive, motivational, and behavioral processes collectively foster higher-order mathematical thinking. These findings provide a broader conceptual understanding of the role of SRL in mathematics education and offer an evidence-based foundation for designing instructional practices that explicitly cultivate students’ self-regulatory capacities while informing future research on technology-enhanced and context-sensitive mathematics learning.